Fourier Transform Infrared (FTIR) spectroscopic determination of soap residues in the refined vegetable oils - Mirghani, Mohamed Elwathig Saeed; Che Man, Yakoob; Selamat, Jinap; Baharin, B. S.; Bakar, Jamilah (Springer Berlin, 2002)
A new analytical method was developed for the determination of soap in palm and groundnut oils by FTIR spectroscopy. Soap from 0 to 80 mg/kg oil was produced in situ in the oils by adding sodium hydroxide. The FTIR spectroscopy was with a sodium chloride transmission cell, and the partial least-squares statistical method was used to calibrate a model for each oil. The accuracy of the method was comparable to that of AOCS Method Cc17-95, with coefficients of determination (R2) of 0.98 and 0.98 for both palm and groundnut oils. The standard errors of calibration were 1.84 and 1.36 for the two oils, respectively. The calibration models were cross-validated, and the R2 of cross-validation and standard errors of cross validation were computed. The standard deviation of the difference for repeatability of the FTIR method was better than that for the chemical method used for determining soap in palm and groundnut oils. With its speed and ease of data manipulation by computer software, FTIR spectroscopy is a possible alternative to the standard wet chemical methods for rapid (2 min) and accurate routine determination of soap in chemically refined vegetable oils